2020
DOI: 10.4314/tzool.v17i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Resistance levels of selected rice genotypes to <i>Sitophilus oryzae</i> L. and <i>Rhyzopertha dominica</i> F. infestations

Abstract: The need to screen new rice genotypes for resistance to stored product insect pests is important to boost production and availability of rice for food security. Therefore, thirteen rice genotypes and varieties included ten interspecific rice genotypes from two crossed parents Oryza sativa (WAB 56-104) and Oryza barthii (IRGC 106107), the two parents and NERICA8 variety were collected from Africa Rice Center, International Institute of Tropical Agriculture (IITA) Ibadan, to examine their resistance level to inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hasil penelitian Gowda et al (2019) juga mengungkapkan tentang kerentanan beras terhadap S. oryzae yang ditentukan oleh jumlah F1 yang banyak dan median waktu perkembangan dari S. oryzae yang singkat. Ajao et al (2019) dan Hendrival et al (2019c) mengemukakan bahwa kerentanan beras dan sorgum terhadap S. oryzae ditentukan oleh jumlah F1 yang banyak dan median waktu perkembangan yang singkat. Kerentanan beras juga dipengaruhi oleh kadar airnya selama penyimpanan.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Hasil penelitian Gowda et al (2019) juga mengungkapkan tentang kerentanan beras terhadap S. oryzae yang ditentukan oleh jumlah F1 yang banyak dan median waktu perkembangan dari S. oryzae yang singkat. Ajao et al (2019) dan Hendrival et al (2019c) mengemukakan bahwa kerentanan beras dan sorgum terhadap S. oryzae ditentukan oleh jumlah F1 yang banyak dan median waktu perkembangan yang singkat. Kerentanan beras juga dipengaruhi oleh kadar airnya selama penyimpanan.…”
Section: Pembahasanunclassified
“…Jumlah F1 yang banyak dan median waktu perkembangan yang singkat dari S. oryzae dapat meningkatkan kerusakan beras. Hasil penelitian Ajao et al (2019) dan Annisa et al (2021) menunjukkan bahwa jumlah F1 yang banyak dan median waktu perkembangan singkat dapat meningkat kerusakan beras. Kerusakan beras berkaitan dengan aktivitas makan dari larva dan imago dengan gejala kerusakan dimulai dengan terbentuknya beberapa lubang tak beraturan bekas gigitan pada bagian permukaan butiran beras.…”
Section: Pembahasanunclassified
“…These findings are somewhat in line with Regmi et al (2017). Ajao et al (2019) who observed that small seed size, tightness of it hull, and reddish caryopsis of a particular variety could explain why it was resistant to S. oryzae attacks. However, the infestation in all cases seems to be less because of the hull covering of grains in rough rice as hull comprises 18 to 25% of the rough rice.…”
Section: Effect Of Genotypes On Mean Number Of Live Weevilsmentioning
confidence: 99%
“…Previous literature suggests that rice breeding for resistance against rice weevils through traditional rice breeding approaches is not helpful [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%